Revelación, iniciativa del encuentro de Dios y el hombre para manifestar el reino de Dios, su justicia y cercanía (2019)
The purpose of this scientific article is to make a historical tour of the Revelation of God, presenting the various forms as God has revealed himself, namely: in the Old Testament, through the Patriarchs and the prophets; in the New Testament, explaining the fullness of the Revelation in Jesus Christ, using the synoptic gospels, the Gospel of St. John, some biblical passages of the letters of St. Paul and the letter of the Acts of the Apostles; with the Vatican Council I., through the document Dei Fides and the Vatican Council II with the Dei Verbum decree. Finally, the conclusions are presented.